Aspartate and glutamate mediate excitatory synaptic transmission in area CA1 of the hippocampus - Fleck, MW (J Neurosci, 1993)
We examined whether L-aspartate (ASP) and L-glutamate (GLU) both function as endogenous neurotransmitters in area CA1 of the rat hippocampus. Radioligand displacement experiments using 3H-DL-alpha- amino-3-hydroxy-5-methylisoxazole-4-propionic acid (3H-AMPA) to label AMPA/kainate receptors and 3H-cis-4-phosphonomethyl-2-piperidine carboxylic acid (3H-CGS-19755) to label NMDA receptors confirmed that GLU (Ki approximately 500 nM) but not ASP (Ki > 1 mM) has high affinity for AMPA/kainate receptors whereas GLU (Ki approximately 250 nM) and ASP (Ki approximately 1.3 microM) both have high affinity for NMDA receptors. Elevating extracellular potassium concentration (50 mM, 1 min) evoked the calcium-dependent release of both ASP (approximately 50% increase) and GLU (approximately 200% increase) from hippocampal slices and from minislices of area CA1. Reducing extracellular glucose concentration (0.2 mM) reduced GLU release, enhanced ASP release, and reduced AMPA/kainate receptor-mediated responses more than NMDA receptor-mediated responses (to 7% and 34% of control, respectively). Fiber volleys, antidromic population spikes, membrane potential, input resistance, and ATP content all were not affected by glucose reduction. Unlike low glucose, the inhibitory neuromodulator adenosine (5 microM), which reduces ASP and GLU release to a similar extent, reduced AMPA/kainate and NMDA receptor-mediated population EPSPs similarly (to 11% and 12% of control, respectively). AMPA/kainate and NMDA receptor- mediated population EPSPs were also similarly reduced by 0.4 microM TTX (to 32% and 22% of control, respectively) and similarly enhanced by 10 microM 4-aminopyridine (to 206% and 248% of control, respectively). Finally, NMDA receptor-mediated EPSCs measured by whole-cell recording decayed faster in low glucose (73 msec vs 54 msec) but not in adenosine (73 msec vs 78 msec). Together, these results confirm that ASP and GLU are both involved in excitatory synaptic transmission at the Schaffer collateral-commissural terminals in area CA1 of the rat hippocampus.